On The Oscilation of the Some Four-dimentional Linear Homogeneous System of Differential Equations - Sahakyan, Georgi
The paper considers the oscillation properties of some a four-dimentional linear homogeneous system of differential equations with a constant sign and continuous on the interval numerical axis coefficients. Հոդվածում դիտարկվում են թվային առանցքի միջակայքի վրա անընդհատ և հաստատուն նշաններով գործակիցներով քառաչափ գծային համասեռ դիֆերենցիալ հավասարումների որոշ համակարգերի օսցիլյացիոն հատկությունները։ В работе рассматриваются oсциляционные свойства некоторых четырехмерных линейных однородных систем дифференциальных уравнений с непрерывными на интервале числовой оси и знакопостоянными коэффициентами.
Keywords: Mathematics